Análise de riscos contra incêndio e pânico: estudo de caso no Hospital Regional Tarcísio Maia em Mossoró/RN - Sousa Neta, Maria do Céu Araújo de (Universidade Federal Rural do Semi-Árido, 2019)
Fire, whether small or large, causes material, ethical and fatal damage. This behavior is exponential, after all the greater the spread of fire the greater the damage and damage to the building. With this in mind, the present work describes an analysis of the fire and panic risk conditions in the public building called the Dr. Tarcísio de Vasconcelos Maia Regional Hospital, located in Mossoró / RN, verifying if the establishment complies with the fire safety regulations. established by NR-23 (Fire Protection Regulatory Standard) and by the Technical Instructions of the Rio Grande do Norte Fire Department (CBMRN). The research was developed through technical visits and on-site analysis, in order to gather data and quantitative information about the existing fire prevention and fire prevention systems and equipment in the building. We used a set of photographic records, survey of the area and surveys of all points of the hospital. The results showed that the establishment has a very poor fire fighting system, with no alarms, emergency signals, fire detection system or water reserve intended for fire fighting purposes. Thus, it is observed that fire-fighting facilities only partially comply with CBMRN instructions and NR-23 guidelines, demonstrating that they do not contribute effectively to the occurrence of accidents and fires.
Monografia
Keywords: Segurança; Proteção; Combate ao incêndio; Norma; Security; Protection; Fire fighting; Standard; ENGENHARIAS::ENGENHARIA CIVIL